PENGARUH EFEKTIVITAS SISTEM KEUANGAN DESA TERHADAP KINERJA APARATUR DESA DENGAN MOTIVASI SEBAGAI PEMODERASI - Theophilia Fina Febrione Leiwakabessy; Rosiana Wonmali; Selva Temalagi (JURNAL ECONOMICA: Media Komunikasi ISEI Riau, 2024)
The aim of this research is to examine village financial system effectiviness on the village government performance with motivation as a moderation variable in Teon Nila Serua (TNS) Subdistrict. The sampling method was purposive sampling with a total sample of 66 respondents from 16 villages in Teon Nila Serua Subdistrict in Maluku Tengah Regency. The data collection technique used was a survey technique using questionnaires. Data analysis used moderated regression analysis. The results of the study explained that village financial system has a poisitive effect on village government performance, which motivation as a moderating variable that strengthens the relationship between village financial system and village government performance.